Dental Applications of Low‐Temperature Nonthermal Plasmas. Issue 3 (18th January 2013) - Kim, Gyoo Cheon; Lee, Hyun Wook; Byun, June Ho; Chung, Jin; Jeon, Young Chan; Lee, Jae Koo
Abstract Oral cavity and teeth are important organs of human body. The attention and cost for dental treatments increase every year. In dental clinics, the most common diseases are dental caries, periodontal disease, and stomatitis. Dental aesthetics such as tooth whitening is one of important part of dental clinics. However, conventional treatment methods in dental clinics have limitations by pain and long‐time treatment. Nonthermal plasmas have shown great potential as noble techniques to dental applications due to safety and multi‐functional effects achieved by the abundant plasma components including charged particles, radiation, and reactive species. Reactive oxygen species generated from plasmas can effectively inhibit pathogen activity. The use of nonthermal plasmas is efficient in treating oral diseases because the construction of the plasma devices allows easy access to the oral cavity. However, few studies have been conducted on the use of plasmas in oral disease. Tooth aesthetics, as well as treatment of oral diseases, are important in determining the quality of human life. Recent studies have shown nonthermal plasmas to have strong tooth‐bleaching effects. Studies on oral care using nonthermal plasmas will significantly contribute to oral health in the future. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>